2016
DOI: 10.1111/micc.12307
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage alterations within the mesenteric lymphatic tissue are associated with impairment of lymphatic pump in metabolic syndrome

Abstract: The intrinsic lymphatic pump is critical to proper lymph transport and is impaired in models of the metabolic syndrome (MetSyn). Lymphatic contractile inhibition under inflammatory conditions has been linked with elevated nitric oxide (NO) production by activated myeloid–derived cells. We utilized a high fructose-fed rat model of MetSyn to test our hypothesis that inhibition of the MLV pump function in MetSyn animals was dependent on NO and was associated with altered macrophage recruitment and polarization wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 83 publications
(184 reference statements)
6
48
1
Order By: Relevance
“…At this condition, one would expect that lymph filling would be decreased, which consequently decreases the phasic contractile frequency and the lymphatic pump flow in the MetSyn condition. In addition, we have shown that resident and innate immune cells, NO production, and expression of cytokines and chemokines modulate lymphatic function during MetSyn and lymphatic inflammation (23, 52). Our current studies on the complete profile of contractile and regulatory proteins of lymphatic vessels from MetSyn and the isolated vessels cultured in HG and insulin conditions and with inflammatory cytokines/chemokines would provide additional insights into the remodeling and function of lymphatics under these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this condition, one would expect that lymph filling would be decreased, which consequently decreases the phasic contractile frequency and the lymphatic pump flow in the MetSyn condition. In addition, we have shown that resident and innate immune cells, NO production, and expression of cytokines and chemokines modulate lymphatic function during MetSyn and lymphatic inflammation (23, 52). Our current studies on the complete profile of contractile and regulatory proteins of lymphatic vessels from MetSyn and the isolated vessels cultured in HG and insulin conditions and with inflammatory cytokines/chemokines would provide additional insights into the remodeling and function of lymphatics under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that insulin resistance is associated with increased macrophage infiltration that is mediated by MCP1 (89). We have shown that MCP1 is induced in LPS‐treated LMCs and is a significant chemoattractant for M1 macrophage polarization in lymphatic vessels and adjacent areas in MetSyn animals (52). Therefore, MCP1 induction is a crucial precursor for more widespread inflammation during insulin resistance, through active recruitment of inflammatory macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats treated with LPS, decreased neutrophil association with mesenteric collecting lymphatics, and increased accumulation of CD163 + CD206 + macrophages (M2 phenotype) accompanied impaired lymphatic contractions, however the cause-effect relationships are not clear (178). In a rat model of metabolic syndrome, macrophages with the M1 phenotype (CD163 + MHCII + ) accumulated near mesenteric lymphatic vessels, and were associated with impaired pumping that could be partially restored with blockade of NOS or K ATP channels (1203). Still, the direct impact of these cells on lymphatic contractile activity remains to be determined.…”
Section: Lymphangions and The Lymphatic Pump Mechanismmentioning
confidence: 99%
“…lipopolysaccharide), and hence initiates the inflammatory immune cascade of macrophage and dendritic cell activation: a cycle of inflammation that likely further alters lymphatic function. 74,75 Lymph leaked in the mesentery is also fatty acid-rich and highly adipogenic, causing expansion of the adipose tissue surrounding the collecting mesenteric vessels. 74,76 In chronic inflammatory bowel diseases from ulcerative colitis to Crohn's disease, lacteals dilate, submucosal edema occurs, and initial lymphatic capillaries proliferate.…”
Section: Lymphangiogenesis In Intestinal Inflammationmentioning
confidence: 99%